Characterization and doping of photochromic BaMgSiO4 with 1st row transition metals and lanthanides - Osmanov, Araz (My University, 2025)
In recent years, there has been an increased focus on the study of tunable inorganic luminescent and photochromic(color-changing) materials. Most of the silicates have poor photochromic properties. However, by doping these particles with specific dopants, these properties can be enhanced. BaMgSiO4 (Barium Magnesium ortho-silicate, shortly BMS) is a member of the silicate salts that suitable for enhancing photochromism using various dopants. Inorganic photochromics provide exceptional heat stability and chemical resistance, making them highly promising for use in multiple applications. The aim of this work is to synthesize radiation-responsive materials and dope them with various transition metals and lanthanides. Testing these dopants on photochromic BMS materials helps to determine their suitability for dose-quantification analyses within the X-ray and UV range. Several first-row transition metals (Fe, Cr, Co, Zn, Cu, V, Ni, and Mn) and a few lanthanides (Eu and Dy) were tested under two different reaction conditions (air and N₂/H₂) with photochromic BMS samples. The results revealed that the N₂/H₂ atmosphere is the most effective reaction condition for synthesis. After selecting the optimal condition, the dopant concentrations were varied—standard (0.05%), halved (0.025%), and doubled (0.1%)—to determine the optimal concentration for each dopant. Further testing confirmed that the synthesized materials are suitable for UV and X-ray radiation detection analyses.
Keywords: dopant, silicates, luminescence, photochromism, UV, X-Ray